Fallopian Tube Papilloma – Case Report of a Rare Tumor - Narasimhaiah, A; Ansari, M; Haritwal, A; Awasthi, S (Kathmandu University Medical Journal, 2015)
Fallopian tube neoplasms are rare. We report a rare case of fallopian tube papilloma discovered incidentally in a 45 year old female, operated for procidentia. Right tube was dilated at the infundibular region, with friable grey white tissue in the lumen. Microscopy showed delicate branching papillae lined by a single layer of epithelium resembling tubal lining. There were no features to suggest a reactive hyperplasia in response to inflammation or of aggressive behaviour. DOI: http://dx.doi.org/10.3126/kumj.v11i3.12515 Kathmandu Univ Med J 2013; 43(3):250-252